2007
DOI: 10.1523/jneurosci.4493-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor (FGF)-2 and FGF Receptor 3 Are Required for the Development of the Substantia Nigra, and FGF-2 Plays a Crucial Role for the Rescue of Dopaminergic Neurons after 6-Hydroxydopamine Lesion

Abstract: Basic fibroblast growth factor (FGF-2) is involved in the development and maintenance of the nervous system. Exogenous administration of FGF-2 increased dopaminergic (DA) graft survival in different animal models of Parkinson's disease. To study the physiological function of the endogenous FGF-2 system, we analyzed the nigrostriatal system of mice lacking FGF-2, mice overexpressing FGF-2, and FGF-receptor-3 (FGFR3)-deficient mice both after development and after 6-hydroxydopamine lesion. FGFR3-deficient mice (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 104 publications
(135 reference statements)
8
89
0
Order By: Relevance
“…Analysis of depletion of DA biomarkers in the striatum showed a trend towards increased loss of DA and DA metabolite content in the transgenic mice relative to controls (Figures 3(a)-(c)) and TH immunostaining in the striatum and SNc further substantiated strong unilateral nigrostriatal damage in th-fgfr1(tk-) mice ( Figure 4). These results are in agreement with previous findings of high susceptibility to 6-OHDA in mice with impaired FGF signaling [36].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Analysis of depletion of DA biomarkers in the striatum showed a trend towards increased loss of DA and DA metabolite content in the transgenic mice relative to controls (Figures 3(a)-(c)) and TH immunostaining in the striatum and SNc further substantiated strong unilateral nigrostriatal damage in th-fgfr1(tk-) mice ( Figure 4). These results are in agreement with previous findings of high susceptibility to 6-OHDA in mice with impaired FGF signaling [36].…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies of FGF-2 KO mice showed an increased susceptibility of DA neurons to 6-OHDA [36]. To assess this possibility in th-fgfr1(tk) mice, we first analyzed rotational movement after administration of apomorphine in the Rotometer Test.…”
Section: Changes In the Nigrostriatal Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, previous studies of mDA NP proliferation mostly relied on animal system(s) or mixed primary cultures, sometimes resulting in conflicting observations. For example, even though bFGF is widely used as a mitogen for NPs (16), mDA NPs increased in bFGF KO mice, whereas mDA NPs decreased in bFGF-overexpressing transgenic mice (15,31). These unexpected results may be caused by multiple compensatory mechanisms in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Besides GDNF and EPO, there are also some other trophic factors used to improve the survival of the grafts, including brain derived neurotrophic factor [30] , fibroblast growth factor (FGF) [31] , nerve growth factor (NGF) [32] and so on. Although studies performed in different laboratories have convincingly established that exposure of DA grafts to some trophic factors during storage prior to transplantation or repeated injection of trophic factors into the implantation site will improve the grafts survival efficaciously, the optimal factors for support of DA grafts should be further identified.…”
Section: Other Trophic Factorsmentioning
confidence: 99%